2015
DOI: 10.3928/1081597x-20150212-01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Keratometry With a Novel Color-LED Corneal Topographer

Abstract: good refractive outcome in cataract and refractive surgery relies on accurate and precise keratometry, particularly in procedures to correct astigmatism. Erroneous keratometric measurements may be a source of intraocular lens (IOL) power calculation errors, 1,2 which lead to postoperative refractive surprises. In addition, appropriate measurement of cylinder axis is important in toric IOL implantation because every degree of misalignment reduces the corrective effect. 3,4The manual Javal-Schiøtz keratometer, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The aim of the current study was to evaluate and compare the keratometric measurements provided by three different commercially available devices in healthy eyes in order to assess the level of interchangeability between them. Previous studies have reported the keratometric outcomes obtained with the Cassini, [9][10][11]13,17,18 Pentacam, 7,[19][20][21] and IOL-Master 22,23 systems in healthy eyes, confirming a good level of intrasession repeatability associated with such measurements. However, the present study is thought to be the first to report a comparison between these three devices.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The aim of the current study was to evaluate and compare the keratometric measurements provided by three different commercially available devices in healthy eyes in order to assess the level of interchangeability between them. Previous studies have reported the keratometric outcomes obtained with the Cassini, [9][10][11]13,17,18 Pentacam, 7,[19][20][21] and IOL-Master 22,23 systems in healthy eyes, confirming a good level of intrasession repeatability associated with such measurements. However, the present study is thought to be the first to report a comparison between these three devices.…”
Section: Discussionmentioning
confidence: 61%
“…These authors only obtained statistically significant differences between devices for J 0 (mean difference: 0.18 D). 30 Klijn et al 10 concluded in another comparative study that there were statistically significant differences between Cassini and Pentacam in terms of the magnitude of astigmatism, but not for the axis of the steepest corneal meridian. Chang et al 4 compared the astigmatic measurements obtained with Pentacam and IOL Master and did not find statistically significant differences between devices in the measurement of the magnitude of corneal astigmatism.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations